2019
DOI: 10.3390/biom9030092
|View full text |Cite
|
Sign up to set email alerts
|

[Pt(O,O′-acac)(γ-acac)(DMS)] Induces Autophagy in Caki-1 Renal Cancer Cells

Abstract: We have demonstrated the cytotoxic effects of [Pt(O,O′-acac)(γ-acac)(dimethyl sulfide (DMS))] on various immortalized cell lines, in primary cultures, and in murine xenograft models in vivo. Recently, we also showed that [Pt(O,O’-acac)(γ-acac)(DMS)] is able to kill Caki-1 renal cells both in vivo and in vitro. In the present paper, apoptotic and autophagic effects of [Pt(O,O′-acac)(γ-acac)(DMS)] and cisplatin were studied and compared using Caki-1 cancerous renal cells. The effects of cisplatin include activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, there are only a few studies on the inhibition of cell growth caused by metal complexes through autophagy induction. For instance, a Pt-based complex, [Pt(O,O’-acac)(γ-acac)(DMS)], induced autophagy in Caki-1 renal cancer cells [ 101 ] and rat B50 neuroblastoma [ 102 ]. Apart from Pt-based agents, Piccolo M et al [ 103 ] and Irace C et al [ 104 ] have certified that the activation of autophagic pathways is a common feature with Ru(III) complexes against breast cancer cells.…”
Section: Ru(ii) Complexesmentioning
confidence: 99%
“…To the best of our knowledge, there are only a few studies on the inhibition of cell growth caused by metal complexes through autophagy induction. For instance, a Pt-based complex, [Pt(O,O’-acac)(γ-acac)(DMS)], induced autophagy in Caki-1 renal cancer cells [ 101 ] and rat B50 neuroblastoma [ 102 ]. Apart from Pt-based agents, Piccolo M et al [ 103 ] and Irace C et al [ 104 ] have certified that the activation of autophagic pathways is a common feature with Ru(III) complexes against breast cancer cells.…”
Section: Ru(ii) Complexesmentioning
confidence: 99%
“…For example, Hongyan et al found that NVP-BEZ235, a novel dual PI3K/mTOR inhibitor, induced cell apoptosis and autophagy in RCC (H. Li et al, 2013 ). Furthermore, Antonaci et al indicated that dimethyl sulfide (DMS) induced autophagy in Caki-1 cells through PI3K/AKT/mTOR/p70S6K pathways ( Antonaci et al, 2019 ). Sunitinib blocking the Akt/mTOR/p70S6K pathway has resulted in autophagy activation in vivo and in vitro (M. L. Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This complex is interesting for its higher anticancer activity, enhanced pharmacokinetics, bio-distribution, and tolerability showed in comparison to cisplatin. This is produced by a non-genomic mechanism of action, as previously demonstrated both in vitro and in vivo [77,78,79,80,81,82]. The observed higher cytotoxicity of Ptac2S with respect to cisplatin in the cisplatin-resistant SKOV-3 cells, evaluated by a preliminary MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay, led us to investigate further the action mechanism of this complex, which is able to overcome cisplatin resistance.…”
Section: The Potential Of An Nmr Metabolomics Approach In Monitorimentioning
confidence: 86%
“…Furthermore, the different lipidic profile in Ptac 2 S, with respect to cisplatin-treated cells, indicates a possible cell death mechanism different from apoptosis (the known cisplatin-induced mechanism of death) [81]. In this context, biological assays have recently demonstrated that Ptac2S induces autophagy in another cisplatin-resistant cancer cell line (Caki-1, a renal cancer cell line) [82]. These findings parallel the results derived through the NMR metabolomic analysis, confirming the power of the technique in the investigation of mechanisms of action.…”
Section: The Potential Of An Nmr Metabolomics Approach In Monitorimentioning
confidence: 99%